Digital Health Technologies in Pediatric Infectious Disease and the Perspective of Patients and Healthcare Professionals: A Review - Alen Sam Saji; Aqsa Komel; Muhammad Hamza Khan; Shreesha Niraula; Babar Naeem; Areeba Ahsan; Achit Kumar Singh; Anum Akbar (Health Science Reports)
ABSTRACT Background and Aims Pediatric infectious diseases pose a global health challenge, causing 13.7 million deaths in 2019 and three million in children under four. Early recognition and management are vital, and challenges in effectively addressing this persist, particularly in resource‐limited areas. Digital health tools, such as telemedicine and mHealth, offer promising solutions. In this review, we aim to evaluate digital health applications in managing pediatric infectious diseases from patient and healthcare perspectives. Methods A literature search was conducted using PubMed, Google Scholar, and Scopus with keywords including “digital health,” “telemedicine,” and “pediatric infectious disease.” Studies published up to January 2024 were included and critically reviewed. Results Digital health technologies aid in real‐time monitoring and early diagnosis of infectious diseases, improving access to specialized care for pediatric populations. Tools like telemedicine and mHealth enhance communication between patients, caregivers, and physicians, facilitating shared decision‐making. Wearable devices and mobile applications enable proactive health management and timely interventions. Despite access challenges in resource‐limited settings, caregivers report benefits such as improved healthcare coordination, reduced delays in care, and better health outcomes for children. Conclusion Digital health shows promise in addressing pediatric infectious disease management, particularly in resource‐limited settings, enhancing outcomes through timely interventions and better communication.